The Influence of Construction Sector Performance on Basic Social Infrastructure Development in Indonesia - Sonny Setyadhy; Pudji Astuty (Return : Study of Management, Economic and Bussines, 2026)
The development of basic social infrastructure, particularly subsidized housing and educational facilities, is a cornerstone of equitable development in Indonesia. Despite increased government spending in these areas, regional disparities in access and quality persist, raising questions about the efficiency of the construction sector as the primary implementing agent. This research aims to analyze the impact of the Indonesian Construction Sector Performance on the availability of subsidized housing and the construction of schools. The research employs a quantitative approach using panel data regression analysis. The sample covers 20 provinces in Indonesia over the period 2018 to 2024, with data sourced from Statistics Indonesia (BPS) and relevant ministries. The results of the panel data regression indicate that the performance of the construction sector has a significant and positive effect on both the availability of subsidized housing and the development of school infrastructure. This finding suggests that improvements in construction sector performance reflected in increased output, productivity, and value-added directly translate into greater physical realization of essential social infrastructure. Provinces with stronger construction sector performance are better positioned to fulfill their targets for subsidized housing provision and the construction of new educational facilities. The research underscores the strategic role of the construction industry as a key enabler in achieving national social development goals and highlights the need for sustained policies to bolster the sector's capacity and reach.